POPULATION POLICY AND ACHIEVEMENT SDGS IN INDONESIA - Trisnawati, Maria; Zid, Muhammad; Muzani, Muzani (Universitas Sebelas Maret (UNS), 2025)
This article looks at the main problems faced in Indonesia regarding population programs, policies taken by the Indonesian Government and the achievement of SDGs in Indonesia. This research uses a descriptive study through literature study using journal and book sources as primary references. The results of the discussion show that Indonesia's natural resource potential is substantial in various fields, as is its population. The main problems were meeting needs within the development framework, issues of environmental damage, and the exponential increase in population, which would impact the next generation's survival. Various programs were launched to control potential environmental damage. Family planning programs, transmigration and education policies are used to anticipate this threat. Environmentally based policies are also not spared. Indonesia's SDGs achievements until 2022 show continued progress, as evidenced by the various awards received by the Indonesian Government for achieving the SDGs.